2022
DOI: 10.35568/abdimas.v4i2.1537
|View full text |Cite
|
Sign up to set email alerts
|

Business Simulation Training Using Monsoonsim

Abstract: Business simulation training has been conducted by the School of Information Technology, Information Systems Department, Ciputra University, using MonsoonSIM. The aim of this activity is to introduce the concept of Enterprise Resource Planning (ERP) to students through virtual business simulation game. This training was conducted online, due to to Covid-19 pandemic.  By using MonsoonSIM software, students can manage a virtual company and learn the company's business processes.  Learnings in this training were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…In fact, gamification strategies used in teaching-learning are innovative in higher education because they generate competitive environments that force the university students to assume a managerial role to act as if they were in a real business practice and participate, as specified by Guzmán Duque and del Moral Pérez [7] and Cristofaro et al [30] in their research. We agree with Dinata et al [5] and Schmeller et al [24] in the ease for the university student to integrate the company in a systemic way, and as evidenced in the research, it offers them an advantage to perform in managerial areas because it will be beneficial to have a disciplinary experience before entering the workplace. For this reason, the graduate profile is improved because competencies are developed for subsequent hiring, coinciding with Navarria et al [6] because managerial practices are facilitated and with Craig et al [8] in the application of knowledge, with skill being an advantage of STEM methodologies.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In fact, gamification strategies used in teaching-learning are innovative in higher education because they generate competitive environments that force the university students to assume a managerial role to act as if they were in a real business practice and participate, as specified by Guzmán Duque and del Moral Pérez [7] and Cristofaro et al [30] in their research. We agree with Dinata et al [5] and Schmeller et al [24] in the ease for the university student to integrate the company in a systemic way, and as evidenced in the research, it offers them an advantage to perform in managerial areas because it will be beneficial to have a disciplinary experience before entering the workplace. For this reason, the graduate profile is improved because competencies are developed for subsequent hiring, coinciding with Navarria et al [6] because managerial practices are facilitated and with Craig et al [8] in the application of knowledge, with skill being an advantage of STEM methodologies.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, the university students indicated that the performance of their functions in their simulated jobs was improved because in the simulator, they applied their knowledge, improved the financial indicators of the simulated companies, and took decisions in environments under pressure, through the analysis of situations and teamwork for the continuous improvement of their companies. This complements the research of García et al [4]; Dinata et al [5]; Guzmán Duque and del Moral Pérez [7]; Meissner et al [22]; and Cristofaro et al [30], who indicate the need to develop managerial competencies that favor the results of organizations through the performance of professionals, and those of Heitzmann et al [1]; Craig et al [8]; and Flegr et al [26], who affirm the need to use technology and STEM methodologies to improve the training of professionals.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations